2017
DOI: 10.1080/16070658.2016.1255483
|View full text |Cite
|
Sign up to set email alerts
|

Mid-upper arm circumference (MUAC) performance versus weight for height in South African children (0–59 months) with acute malnutrition

Abstract: Objectives:The objective of this study was to compare mid upper arm circumference (MUAC) and weight for height (W/H) as indices of acute malnutrition in children aged 0-59 months in South Africa. Design: A cross-sectional weighted survey of households was performed. Subjects and setting: Children aged 0-59 months and their mothers/caregivers were included in the study in iLembe district conducted between April and September 2014. Outcome measures: W/H and MUAC were measured and z-scores were calculated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Although the level of wasting was low in a study by Dukhi N who compared these two methods for evaluating the nutritional status of under 5 children the results revealed that more children (44) were identified to be malnourished based on WHZ score as compared to MUAC (38). This study showed WHZ method as a more sensitive measure of child malnutrition as more than double children identified to having SAM compared to MUAC 16…”
Section: Discussionmentioning
confidence: 79%
“…Although the level of wasting was low in a study by Dukhi N who compared these two methods for evaluating the nutritional status of under 5 children the results revealed that more children (44) were identified to be malnourished based on WHZ score as compared to MUAC (38). This study showed WHZ method as a more sensitive measure of child malnutrition as more than double children identified to having SAM compared to MUAC 16…”
Section: Discussionmentioning
confidence: 79%
“…It was noticed that age plays a significant role in MUAC and weight for height discrepancies, as it is associated with food insecurity (Young and Jaspers 2009). Among the young children wasting is indicative of disease together with poor feeding practices (Dukhi et al 2017). It was also observed that during a period of food insecurity, older children are likely to experience more acute malnutrition (Bern and Nathanail 1995) than younger ones.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Dukhi et al, found W/H to be a more sensitive measure. 7 At a facility level W/H is considered the anthropometric measure of choice in children aged 0-59 months as nurses are trained in obtaining this measure. At the household level MUAC is preferred as a quick and easy measuring tool.…”
Section: Discussionmentioning
confidence: 99%